The aroma analysis of asparagus tea processed from different parts of green asparagus (Asparagus officinalis L.). Issue 1 (7th December 2021) - Xue, Junxiu; Zhang, Xinfu; Cheng, Chenxia; Sun, Chao; Yang, Shaolan
Abstract: Asparagus is a perennial herb rich in multiple nutrients; however, the utilization of asparagus is lower on account of one‐third part of the asparagus often be discarded as a by‐product at harvest in order to standardize the length for market. In this study, asparagus spears were divided into tip (top of the spear, 5 cm), mid (intermediate of the spear, 5 cm), and base (rest of the spear, 5 cm) parts, and the mid part and base part were cut into as 2–3 cm length. As following, the three parts of asparagus spears were processed into tea with green tea processing craft, respectively. Electronic nose and GC‐MS analyses were used to investigate the aroma components of three asparagus teas. A total of 59 components were detected, among which there were 37, 43, and 50 components in the tip, mid, and base asparagus tea, respectively. According to the electronic nose analysis and GC‐MS analysis, we speculate aldehydes, alkanes, and ketone were the main aroma components of asparagus tea. And the different aroma components among the three asparagus teas might be caused by the different spear parts of asparagus. The sensory evaluation score of the mid asparagus tea was 88.54 ± 0.33, which was highest among the three teas. The results indicated that mid asparagus tea might be more popular with consumers. Practical applications: Asparagus ( Asparagus officinalis L.) were divided into tip, mid, and base parts, and every part was processed into tea respectively. The process optimization and aroma analysis could improve the utilization rate of asparagus and also provides a basis for clarifying the specific volatile of asparagus tea.